(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Kerala’s growth and development circuit has been uniquely shaped by the large amount of international migration and remittance influxes. This study analyses household consumption patterns in Kerala over two decades (2003–2023) using data from the Kerala Migration Surveys of 2003, 2008, 2013, 2018, and 2023. The research paper concentrates only on two objectives: examining how remittances amount that influence household consumption patterns and comparing the changes in expenditure preferences across varieties such as food, housing, education, health, and consumer durables. The findings show that remittance inflows increased more than elevenfold in absolute terms, while their share in Net State Domestic Product (NSDP) fluctuated, peaking in 2008 and partially recovering by 2023. Household spending patterns shifted from basic consumption toward housing, savings, investments, debt repayment, and consumer durables, reflecting a structural changeover in expenditure preferences. Pearson correlation analysis indicates a negative association; however, results should be interpreted cautiously due to the limited number of observations. Chi-Square and Symmetric Measures prove significant differences in expenditure patterns over time. The Kerala Migration directions also show a gradual diversification from GCC to Non-GCC Countries and a slowing increase of emigrants. The research underscores the evolving role of remittance amounts in boosting asset accumulation, financial stability, and human capital investment, the study provides useful insights into the relationship between remittances and household consumption. The findings are consistent with migration–development theories that highlight a transition from consumption smoothing to asset accumulation as remittance dependence matures.